LYN-RADS: uma proposta de sistema de informação ecográfica para linfonodos da região cervical e estratificação para risco de câncer - Barros, Larissa Vasconcelos (2024)
Lymph nodes are small oval structures that play important roles in our body's defense system and about a third of them are in the cervical region. As they are mostly at more superficial levels of the body, the ultrasound examination of the cervical region carried out with a high frequency linear transducer (above 10 MHz) and by an experienced operator is capable of easily identifying the lymph nodes. Some ultrasound criteria are used to differentiate a lymph node between benign and suspicious, such as number, dimensions, shape, hilum and cortex, presence of necrosis, calcification, extracapsular dissemination and vascularization pattern. Our aim was to develop a standard and practical lexicon for describing the sonographic characteristics of cervical lymph nodes, the Lymph Node Imaging-Reporting and Data System (LYN-RADS), with the ultimate intention of applying it to risk stratification and node screening for consistent follow-up in clinical practice. With this in mind, after an extensive literature review, we created a lexicon with the main echographic characteristics of lymph nodes and assigned them a score according to their degree of suspicion based on our statistical analysis carried out with multiple logistic regression, Decision Tree and Receiver Operation Characteristic (ROC) curve, adopting 95% confidence intervals. Lymph nodes with a score lower than 4 were considered benign; and as suspicious lymph nodes those with a score greater than or equal to 4. In the next step, an association was made with the cytological result of the Fine Needle Aspiration Cytology (FNAC) of each lymph node. The pathologists who analyzed the samples were not present on the day the material was collected and did not have access to the ultrasound images of the cervical lymph nodes, just as the radiologists did not have access to the cytopathological results when evaluating the ultrasound images in the database. We retrospectively evaluated 200 lymph nodes that underwent FNAC in a specific Hospital in Fortaleza-CE. This lexicon had a sensitivity of 81.63% and a specificity of 94.70% in this study. Therefore, the LYN-RADS developed by our study showed that more than 75% of FNACs performed on the evaluated lymph nodes were unnecessary, since these lymph nodes would receive scores lower than 4 points, being considered benign and could only be monitored with ultrasound follow-up, thus dispensing with FNAB, which is an invasive and uncomfortable examination for the patient.